2014
DOI: 10.1063/1.4891306
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Brownian Dynamics simulations of clathrin cage formation

Abstract: (2013)] has shown intriguing abilities to accurately describe potential energy surfaces in various notoriously difficult cases. The question that still remained open is to what extend the accuracy and the stability of the method is due to the special choice of orbital-relaxation treatment. In this paper we introduce orbital relaxation in terms of Brueckner orbitals, orbital optimization, and projective singles into the distinguishable cluster approximation and investigate its importance in single-and multirefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 76 publications
(22 reference statements)
0
36
0
Order By: Relevance
“…Although the principles behind Eqs. (13) and (14) are well known in the literature 31 and many authors have numerically tested the drift terms, 27,30,32,39 to the best of our knowledge, this is the first time that a Langevin equation for a confined uniaxial particle is explicitly in this discretized complete form, fully embodying roto-translational coupling.…”
Section: A Langevin Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the principles behind Eqs. (13) and (14) are well known in the literature 31 and many authors have numerically tested the drift terms, 27,30,32,39 to the best of our knowledge, this is the first time that a Langevin equation for a confined uniaxial particle is explicitly in this discretized complete form, fully embodying roto-translational coupling.…”
Section: A Langevin Equationmentioning
confidence: 99%
“…22 Many examples of numerical simulations on Brownian non-spherical particles are reported in the recent literature. Brownian dynamics simulations of unbounded suspensions of rod-like particles [23][24][25][26][27] and arbitrarily shaped particles [28][29][30] have been carried out for different volume fractions, ranging from dilute to concentrated regimes, although interparticle hydrodynamic interactions are often neglected. The inclusion of hydrodynamic interactions gives rise to "corrective terms" in the Brownian dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…3.3(b). For completeness a 'random' body-fixed unit vector parallel that act as rigid units, thereby opening routes to study the dynamics of their self-assembly into ordered aggregates [86]. Bonds between the particles are readily included in the interaction potential, thereby creating patchy-particle 'molecules'.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…These authors did include metric and drift corrections and found that the propagator differs from the intuitively expected ∆a = (∂a/∂φ b )∆φ b [55,56,57,58,131]. This technique was recently successfully used to simulate the self-assembly of anisotropic particles into well-ordered structures [86], but it is fairly involved and requires multiple Taylor expansions to solve weak singularities.…”
Section: Brownian Dynamics Algorithm 45mentioning
confidence: 99%
See 1 more Smart Citation